(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Total serum sialic acid (TSA) and lipid associated sialic acid (LSA) are found to be increased in different neoplastic diseases .The present study was undertaken to study the changes in the concentration of TSA and LSA in patients with different types of brain tumors before and after surgical removal of brain tumor. Methods: TSA and LSA levels have been estimated in serum of patients with benign brain tumors (n=28) and malignant brain tumors (n=31) in addition to healthy controls (n=34).Also the TSA and LSA measured in the patients (7) days after surgical removal of the tumor. Results: Data analysis reflects a significant increase (p<0.05) in the TSA and LSA in the malignant tumor patients as compared with healthy controls. The results revealed a significant decrease (p<0.05) in the TSA but not LSA (7) days after operation. Conclusions: It has concluded that there is a correlation between the type of tumor and the concentration of TSA and LASA. The surgical removal of the tumor leads to decrease in TSA and LASA in the serum. Keywords: Brain tumor, Cancer, Sialic acid, Lipid associated sialic acid Iraqi J Med Sci, 2004; Vol. 3 (1): 29-31